The role of sports mega events in the sustainable development of cities: a systematic review / Changqing Xiang ... [et al.] - Changqing, Xiang; Wenting, Dong; Tengku Kamalden, Tengku Fadilah; Ismail, Normala; Jie, Zhao; Xiaoming, yang; Hua, Luo (Faculty of Sports Science and Recreation, 2023)
Despite the known contribution of sports events to cities, especially affected by COVID-19 pandemic, residents hold different attitudes to this, for some citizens, sports events continue to play a vital role in cities sustainable development and may contribute to improved life condition and infrastructure in cities, but others do not think so. Although the benefits of sports events are commonly reported, the reasons why some cities and citizens willing to hold sports events are not well understood. This systematic review aimed to identify studies from the literature that the importance of sport mega-events in cities sustainable development synthesize and discuss the reasons for willing to hold sports events reported in the literature. Searches of the e-journal databases including Science Direct, Sport Discus, Scopus, Social Science Citation Index and Arts & Humanities Citation Index were performed. Studies were included that evaluated importance of sports events in cities sustainable development and residents' attitudes because this is the key point to promote sports events development. The studies included in this review used qualitative, quantitative or mixed methods designs, were peer reviewed, and were published in the English language before the search date. Results: There are 2036 studies identified and after exclusions 30 studies were included in the review (9 qualitative, 10 quantitative, and 11 mixed methods). The review presents several features and findings from the studies, including a description and systematization the role of sports mega-events for cities sustainable development and the main reasons that cities and citizens willing to hold sports events (e.g. increasing job chances, improving the visibility of the city, and taking advantage of opportunities to develop economy). The finding suggest that sports events are an integral part of sustainable development of the city, and sports mega-events were identified as contributing to the city development. Cities and citizens can benefit from various sports events with regard to their development. Sports events play an important role in the sustainable development of cities, and contribute to the political, economic and cultural development of the city. The development of sports events and strategies to promote sustainable urban development should focus on these aspects after COVID-19.